Analysis of Load Sharing of Planetary Gear Train Considering the Flexibility of Planet Carrier - Xu Hongbin; Xu Taojin; Huang Yongping (Jixie chuandong)
The principle and application of flexible file generation process and gear slicing in the SIMPACK are introduced. Taking a 7MW wind turbine gearbox as an example,a multi- body dynamics model of the first planetary gear train is built in the SIMPACK. In the modeling process,the planet carrier is considered as flexible body and the gears are split into five smaller segments. The deformation of the planet carrier and the load sharing behavior is analyzed when gearbox is at rated input power and speed. The results show that,when using the accurate 3D model of planet carrier and considering the flexible of it,the deformation of the planet carrier is effected by the variable engagement force and tooth deformation. The deformation of the planet carrier connected to different pin is different,but the torsional deformation of input stage is larger than output stage generally. Comparing the deformation of the planet carrier with the load sharing coefficient,it is found that the torsional deformation of the planet carrier is the main factor effect the uneven load coefficient of the gear. The results can be a reference of the structural optimization design of planet carrier.